THE EFFECT OF LANGUAGE ATTITUDE AND GENDER: CULTURAL AND LEVEL OF EDUCATION - INDRA JAYANTI DAMANIK; ANITA PURBA (JURNAL ILMIAH KOHESI, 2019)
Learning a language is influenced by a variety of factors. Two of the most important of which are the learner’s attitude and perception toward the target language. These are the concepts which have been the focal points of sociolinguists as far as learner behavior is concerned. Therefore, this study was conducted in an attempt to provide an account of the previous studies conducted on attitude and perception and their impacts on learners’ learning abilities. Motivation, as a determining factor in learning, in relation to language performance is going to be discussed as well. Additionally, different frameworks for the classification of learners’ belief will be discussed and relevant conclusions will be drawn.